2006
DOI: 10.1556/avet.54.2006.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in canine atopic dermatitis: A review

Abstract: Atopic dermatitis (AD) is a genetically predisposed inflammatory and pruritic allergic skin disease with characteristic clinical features. New results on the pathogenesis and therapeutic aspects are discussed in this review. IgE-mediated hypersensitivity may be involved in the largest subset of atopic patients, yet there is another subset for which such involvement cannot be documented. Alterations in epidermal barrier function, priming of cutaneous antigen-presenting cells with IgE, intrinsic keratinocyte def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…3,[5][6][7][8] Pruritic skin diseases, such as allergic hypersensitivities that were present in 16 of the 20 dogs in this study, result in self-trauma and damage to the barrier function of the epidermis. 51 Furthermore, S. intermedius has been shown to adhere to corneocytes preferentially in dogs with atopic dermatitis. 52 In the study reported here, culture of S. intermedius from 15 (75%) of 20 dogs with superficial and deep pyoderma is in agreement with results of previously reported studies, [10][11][12] indicating that this organism is the most common canine skin pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…3,[5][6][7][8] Pruritic skin diseases, such as allergic hypersensitivities that were present in 16 of the 20 dogs in this study, result in self-trauma and damage to the barrier function of the epidermis. 51 Furthermore, S. intermedius has been shown to adhere to corneocytes preferentially in dogs with atopic dermatitis. 52 In the study reported here, culture of S. intermedius from 15 (75%) of 20 dogs with superficial and deep pyoderma is in agreement with results of previously reported studies, [10][11][12] indicating that this organism is the most common canine skin pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a strong link between dog breed and the development of AD, suggesting a ge-netic link does exist 165,166 and diagnostic testing could be useful. A recent study by Wood et al 167 evaluated a variety of single nucleotide polymorphisms in 25 candidate genes in 242 dogs with AD and 417 healthy control dogs across several breeds and regions.…”
Section: Diagnosis Of Canine Admentioning
confidence: 99%
“…Glucocorticoids (GCs) are important modulators of immune cell functions (Sternberg, 2006). Due to their well-known immunosuppressive and anti-inflammatory properties, synthetic GCs are widely used in clinical practice and are effective in the treatment of autoimmune disease (Sathasivam, 2008), immunological rejection (Everson et al 2003), atopic inflammatory disease (Tarpataki , 2006) and acute critical illness (Minneci et al 2004;Rady et al 2006).…”
Section: Introductionmentioning
confidence: 99%